PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBEREDS HEADS TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDN 001 SAWAH - Rosnita, Erni; Marhadi, Hendri; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstrakThe study was based on the low grade IV student learning outcomes Sawah Elementary School 001. Of the 24 students who achieved KKM only 10 people. The purpose of this research is to improve student learning outcomes Elementary School fourth grade 001 Sawah with the application of cooperative learning model Numbereds Heads Together. The results of the activity of the teacher 's first meeting of the first cycle first cycle percentage 60 % with enough categories, increased in the second meeting to be 70 % better categorized. At the first meeting of the second cycle increased with the percentage of 77.5 % in both categories, and the second meeting of the second cycle of 92.5 % categorized very well . The results of the first cycle activity students first encounter the first cycle percentage 60 % categorized enough, increasing the percentage of 67.5 % meeting both categorized enough. At the first meeting of the second cycle increased to 77.5 % categorized either. At the second meeting of the second cycle increased to 90 % categorized very well. Mastery learning students on the basis of scores of students who completed the 10 students who did not complete while 14 students, with classical completeness 41.67 % ( not finished). At the end of the first cycle of repeat students who complete 17 incomplete whereas 7 students, with classical completeness 66.66 % ( not finished). At the end of the second cycle replications increased thoroughness, students who completed the 22 students who did not complete while 2 students, with classical completeness of 87.5 % ( completed ). It can be concluded that with the implementation of cooperative learning model Numbereds Heads Together to improve learning outcomes IPS Elementary School fourth grade students 001 Sawah. Keywords: Cooperatif Numbereds Heads Together, The Result Of Social Studies